393 Harnessing the potential of transcriptional adaptation as a mechanism for rare Amyotrophic lateral sclerosis - Adriana Morales Gomez; Nathan Staff; Stephen C. Ekker (Journal of Clinical and Translational Science, 2024)
OBJECTIVES/GOALS: Transcriptional adaptation is a phenomenon in which a mutation in one gene leads to the genetic compensation of another homogenous gene. Understanding the mechanism of transcriptional adaptation may contribute to an explanation for variation in clinical manifestations of rare Amyotrophic lateral sclerosis patient phenotypes. METHODS/STUDY POPULATION: The presence of a premature termination codon triggers transcriptional activation. Therefore, we utilized CRISPR-Cas9 tool to generate a premature termination codon in CHCHD10 gene in multiple types of cells, including induced pluripotent stem cells derived from patient samples with known CHCHD10 mutations causative for Amyotrophic lateral sclerosis. CRISPR-Cas9 tool was delivered via ribonucleoprotein electroporation and transfect cell’s DNA was sequenced to validate gene editing. To confirm transcriptional adaption, changes in levels of protein and gene expression will be measured via immunoblot and quantification of CHCHD10 and CHCHCD2 from whole cells lysates of the edited cells. RESULTS/ANTICIPATED RESULTS: We anticipate that CHCHD2 transcriptional adaptation can functionally compensate for the locus loss of function of CHCHD10. This mechanism of transcriptional adaptation may contribute to an explanation for variation in clinical manifestations of patient phenotypes. DISCUSSION/SIGNIFICANCE: Our approach would advance discovery science towards by exploring transcriptional adaptation mechanism in humans, which can lead to novel therapies for rare Amyotrophic lateral sclerosis, such as CHCHD10.